Reduction of Cogging Torque Technique in Sequential of Permanent Magnet Flux Switching Motor - Hasan, Noor Faradilah Afiqah; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2022)
A study of several electric motors has been conducted on permanent magnet flux switching motors because it shows an excellent performance such as higher torque density, high efficiency, low vibration, and ease to control. However, this motor design encountered high cogging torque due to the interchange of permanent magnets in stator and rotor teeth. This study aims to improve the cogging torque of single-phase 4S-8P PM-FSM by implementing a reduction cogging torque technique in sequential. The initial design of 4S/8P PM-FSM is analyzed using JMAG Designer software. Three classical cogging torque reduction techniques will be applied to the motor notching, chamfering, and pole-pairing. These three classical cogging torque techniques will be tested individually, and the lowest cogging torque produced in each result will be selected for the next sequential. The performance of cogging torque is minimized from an initial value of as much as 35% from the initial design, which is from 1.7722 Nm to 1.1116 Nm.